2013
DOI: 10.1155/2013/574937
|View full text |Cite
|
Sign up to set email alerts
|

Targeted versus Universal Neonatal Hearing Screening in a Single Egyptian Center

Abstract: Aim. To compare targeted neonatal hearing screening (TNHS) and universal neonatal hearing screening (UNHS) since many developing countries, including Egypt, implement selective screening for high-risk neonates. Methods. 150 neonates were assessed; 50 full terms consecutively admitted to the well-baby nursery and 100 neonates consecutively admitted to neonatal intensive care unit (NICU), Ain Shams University. Patients were further subdivided into high-risk group which included 50 neonates with multiple risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(25 reference statements)
1
11
0
Order By: Relevance
“…Association of family history of hearing loss with neonatal hearing loss was found to be significant (p value <0.001) in our study. This is comparable to the findings of Nie W, et al [7] In another study carried out by Imam S.S. et al [5] in Egypt, consanguinity was the most prevalent risk factor for hearing loss comprising 46%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Association of family history of hearing loss with neonatal hearing loss was found to be significant (p value <0.001) in our study. This is comparable to the findings of Nie W, et al [7] In another study carried out by Imam S.S. et al [5] in Egypt, consanguinity was the most prevalent risk factor for hearing loss comprising 46%.…”
Section: Discussionsupporting
confidence: 90%
“…[5] However, choosing any option needs realistic assessment of the magnitude of the problem in terms of prevalence of specific type of hard of hearing as well as the risk factors operating in that specific context. In this regard, the present study, a cross-sectional study was carried out to study the prevalence of neonatal hearing loss and study the association of various risk factors with the hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown in Egypt 27 and India 28 that targeted newborn hearing screening is another valuable option, especially when resources are constrained 7 . However, our targeted analysis yielded a very low prevalence (0.3%) compared with other targeted screening studies (2.0–4.0%) 1 , 2 .…”
Section: Discussionmentioning
confidence: 99%
“…18.20 The risk factors for using ototoxic drugs during important for the prevention of disability and for improving people's quality of life. 3,18 The limitation of this study is that there are actually many risk factors associated with the occurrence of congenital deafness, but in this study only a few factors were analyzed due to limited data on medical records and the limited accuracy of the history data due to not being an objective examination result. Some of the factors that were not included in this study included postnatal risk factors such as meningitis and postnatal temporal trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the Chi square test showed that there was no significant relationship between family history and congenital deafness with the results of OAE and ABRexaminations (p = 0.715). This may be due to in-depth family history history or because the child's parents do not understand the definition of these risk factors, the small number of samples and the absence of objective examinations and genetic examinations to confirm the presence of these risk factors 3,20.…”
mentioning
confidence: 99%